Network and information systems (nis) regulations - a pocket guide for digital service providers. - CALDER, ALAN (IT GOVERNANCE LTD, 2018)
This pocket guide is a primer for any DSPs (digital service providers) that needs to comply with the NIS Regulations, and explores who they are, and why the NIS Regulations are different for them.